Epigenetics - Pandey, Subhash C. (International review of neurobiology, 2014)
This well-established international series examines major areas of basic and clinical research within neuroscience, as well as emerging and promising subfields. This volume concentrates on Epigenetics This book looks at Epigeneticsin the light of the newest scholarly discoveries and insights.